2017
DOI: 10.1128/msystems.00074-17
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Evolution of Group B Streptococcus Hypervirulent Clonal Complex 17 Unveils New Pathoadaptive Mutations

Abstract: The incidence of group B Streptococcus (GBS) neonatal disease continues to be a significant cause of concern worldwide. Strains belonging to clonal complex 17 (CC17) are the most frequently responsible for GBS infections in neonates, especially among late-onset disease cases. Therefore, we undertook the largest genomic study of GBS CC17 strains to date to decipher the genetic bases of their remarkable colonization and infection ability. We show that crucial functions involved in different steps of the coloniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 64 publications
3
40
0
Order By: Relevance
“…GBS strains lacking a functional CovR ( covR) cause significantly greater cytotoxicity in neutrophils compared to wildtype (WT) GBS and isogenic non-pigmented/non-hemolytic mutants due to enhanced production of Granadaene (Lamy et al, 2004;Jiang et al, 2005;Rajagopal et al, 2006;Boldenow et al, 2016). Furthermore, GBS strains lacking CovR have been identified and isolated from women in preterm labor (Whidbey et al, 2013) and from patients with other GBS infectious morbidities (Sendi et al, 2009;Lupo et al, 2014;Almeida et al, 2015Almeida et al, , 2017Whidbey et al, 2015a). We hypothesized that L. lactis pcylX-K, which lacks transcriptional repressors specific to the cyl operon, would induce neutrophil cytotoxicity similar to GBS covR.…”
Section: Resultsmentioning
confidence: 99%
“…GBS strains lacking a functional CovR ( covR) cause significantly greater cytotoxicity in neutrophils compared to wildtype (WT) GBS and isogenic non-pigmented/non-hemolytic mutants due to enhanced production of Granadaene (Lamy et al, 2004;Jiang et al, 2005;Rajagopal et al, 2006;Boldenow et al, 2016). Furthermore, GBS strains lacking CovR have been identified and isolated from women in preterm labor (Whidbey et al, 2013) and from patients with other GBS infectious morbidities (Sendi et al, 2009;Lupo et al, 2014;Almeida et al, 2015Almeida et al, , 2017Whidbey et al, 2015a). We hypothesized that L. lactis pcylX-K, which lacks transcriptional repressors specific to the cyl operon, would induce neutrophil cytotoxicity similar to GBS covR.…”
Section: Resultsmentioning
confidence: 99%
“…To complement the analysis, published whole genome sequence data of 4112 GBS isolates from previous studies was also included in this work (S5 Table). This was composed of isolates described by Da Cunha et al (n=228) [16], Rosini et al (n=127) [37], Flores et al (n=184) [33], Seale et al (n=1034) [38], Teatero et al (n=77) [20], Campisi et al (n=84) [22, 36], Almeida et al (n=192) [21, 23], Metcalf et al (n=2025) [15], and Kalimuddin et al (n=161) [24].…”
Section: Methodsmentioning
confidence: 99%
“…Also, work by Almeida et al reported a collection of mutations in the covS gene. These were primarily single amino acid substitutions (Thr43Ile, Ala87Val, Gly133Ser, His209Asn, Trp297Leu, and Glu337Ser) and the one double substitution (Trp297Cys and Gly298Trp) 41 . None of these amino acid changes were predicted amino acid changes in the covR and covS mutations found in our isolates suggesting mutations of covR and covS may occur in multiple locations in these genes.…”
Section: Discussionmentioning
confidence: 99%